Service Quality and Social Media Marketing Activities as Determinants of Revisit Intention: Customer Satisfaction as an Intervening Variable - Regina; Agus Setyo Pranowo; Sufrin Hannan (PT. Maju Malaqbi Makkarana, 2026)
This study examines service quality and social media marketing activities as determinants of revisit intention, with customer satisfaction as an intervening variable at Flui Restaurant & Cafe Bogor. The research was motivated by the decline in customer visits despite the restaurant’s strategic location, unique waterfall concept, and active social media promotion. A quantitative explanatory approach was applied using a cross-sectional survey of 400 customers who had visited Flui Restaurant & Cafe Bogor. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using Structural Equation Modeling with LISREL 8.80. The results show that service quality has a positive and significant effect on customer satisfaction and revisit intention. Social media marketing activities also have a positive and significant effect on customer satisfaction and revisit intention. Furthermore, customer satisfaction significantly influences revisit intention and partially mediates the relationship between service quality and revisit intention, as well as between social media marketing activities and revisit intention. These findings indicate that increasing revisit intention requires an integrated strategy involving consistent service quality, interactive social media marketing, and customer satisfaction improvement